2019
DOI: 10.1002/ijgo.12785
|View full text |Cite
|
Sign up to set email alerts
|

The ability of thromboelastography parameters to predict severe pre‐eclampsia when measured during early pregnancy

Abstract: Objective To examine the predictive value of thromboelastography parameters during early pregnancy as potential markers of severe pre‐eclampsia during late pregnancy. Methods An observational retrospective case–control study was conducted among pregnant women who attended a single hospital in Shanghai, China, between July 1, 2016, and February 31, 2018. Data were obtained from medical records and a structured questionnaire completed by the participants. Thromboelastography parameters included time r; time k; α… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 24 publications
0
16
0
1
Order By: Relevance
“…Multiple studies used TEG to successfully monitor hemostatic changes in preeclampsia/ eclampsia, and have shown that the TEG CI can be used as an early predictor of severe preeclampsia. [40][41][42][43][44] They demonstrated that women with mild preeclampsia are hypercoagulable when compared with healthy pregnant women, but as the severity of preeclampsia worsens, blood coagulability decreases, and severe preeclamptic women with a platelet count < 100 000/mm 3 were significantly more hypocoagulable across all TEG parameters compared with healthy pregnant women and women with less severe preeclampsia. 40 Sharma et al and Morgan et al found a trend of increasing hypercoagulability with increasing body mass index (BMI); whereas Sharma et al found significant differences with TEG, Morgan et al did not.…”
Section: Teg In Patients At Risk For Thrombosismentioning
confidence: 99%
“…Multiple studies used TEG to successfully monitor hemostatic changes in preeclampsia/ eclampsia, and have shown that the TEG CI can be used as an early predictor of severe preeclampsia. [40][41][42][43][44] They demonstrated that women with mild preeclampsia are hypercoagulable when compared with healthy pregnant women, but as the severity of preeclampsia worsens, blood coagulability decreases, and severe preeclamptic women with a platelet count < 100 000/mm 3 were significantly more hypocoagulable across all TEG parameters compared with healthy pregnant women and women with less severe preeclampsia. 40 Sharma et al and Morgan et al found a trend of increasing hypercoagulability with increasing body mass index (BMI); whereas Sharma et al found significant differences with TEG, Morgan et al did not.…”
Section: Teg In Patients At Risk For Thrombosismentioning
confidence: 99%
“…Interestingly, completely opposite changes of TEG parameters were observed in different studies. In the work by Wang et al, 16,20 the mean values for R and K among the women with PE were higher than those of the control group; the mean values for MA and α‐angle were lower in the PE group than in the control group. These findings were similar to ours (Figure 1 and Table ), implying coagulation damage that may be related with increased tissue factor and consumption of clotting factors in PE patients 16 .…”
Section: Discussionmentioning
confidence: 81%
“…Interestingly, the article by Shupletsova et al reported that the GDM patients experiencing cerebral ischemia (CI) in newborn infants were more likely to present decreased R and K and increased MA and α‐angle than the GDM patients who ended up with no obvious adverse outcomes, implying that glycemia during pregnancy may be involved in programming the development of coagulation disorders and could have effects on TEG results. Unlike GH and GDM, more studies were focused on the direct comparison of TEG parameters between normal and PE pregnancies 16,20,21 . Interestingly, completely opposite changes of TEG parameters were observed in different studies.…”
Section: Discussionmentioning
confidence: 99%
“…47,48,50 Moreover, more severe forms of preeclampsia appear to be associated with a distinct laboratory haemostatic profile relative to that observed in individuals with less severe manifestations of this disease. 40,121,122 The clinical implications of these observations remain to be determined.…”
Section: Haemostatic Derangements As Markers Of Disease Severity In Pmentioning
confidence: 99%